Development of Mathematics Teaching Materials in the Context of Land Transportation Tickets for High-Level Thinking - Malalina, Malalina; Yenni, Rika Firma (Universitas Sarjanawiyata Tamansiswa, 2026)
The development of mathematics teaching materials in the context of land transportation tickets is essential because it is close to participants’ daily lives and includes comparative materials on direct proportion, which can be used to optimize high-level thinking. This research aims to develop mathematics teaching materials in the context of land transportation tickets that are valid, practical, and have a potential effect on high-level thinking skills. The method employed by the development study includes preliminary and formative evaluation stages. The subjects of this study are students at SMP Negeri 3 South Pemulutan and SMP Negeri 47 Palembang. Data collection techniques use walkthroughs, interviews, observations, and tests. Qualitative descriptive techniques were used to analyze the data obtained. The results of expert validation show that the developed teaching materials are deemed valid in terms of content, construction, and language. The small group stage demonstrates that the teaching materials are practical, as students do not encounter difficulty using them during the learning process. The results of the field test showed the potential impact of teaching materials on students’ high-level thinking skills, as measured by indicators of analysis, evaluation, and creation. This research produces mathematics teaching materials in the context of land transportation tickets that are valid, practical, and have the potential to foster high-level thinking in the ability to analyze, evaluate, and create. It is expected to be used in learning to improve students’ high-level thinking skills through the context of land transportation tickets.